Pencegahan Stunting melalui Kader Bina Keluarga Balita (BKB) di Dusun Ponoradan Desa Tanjungsari Kecamatan Tlogomulyo - Husna Nashihin; Yenny Aulia Rachman; Ulya Muyasaroh; Ahmad Aji Pangestu; Triana Hermawati (Jurnal Pengabdian Masyarakat Bestari, 2022)
This Community Service Research was motivated by 4 background problems, namely the high prevalence of stunting in Indonesia which reached 27.7%, the high stunting rate in Ponorad Village and Tanjungsari Village, Tlogomulyo District, the need for stunting prevention methods in Ponorad Hamlet and Tanjungsari Village, Tlogomulyo District, Bina The Toddler Family (BKB) is a good stunting prevention method to be applied in Ponoradan Hamlet and Tanjungsari Village, Tlogomulyo District. The results of this study indicate a decrease in stunting rates in Ponorad Hamlet and Tanjungsari Village, Tlogomulyo District through the application of Toddler Family Development (BKB). The continuity of this research is indicated by the formation of BKB cadres in Ponoradan Hamlet, the formation of a BKB cadre structure in Ponoradan Hamlet, the formation of a SK (Decree) for BKB Kasih Bunda in Ponoradan Hamlet, Ponoradan BKB cadres have received basic training, the implementation of BKB in Ponoradan Hamlet has received support full of village officials, the tools needed for the implementation of BKB activities have been prepared, and the Ponoradan Hamlet BKB will be held every month in conjunction with Posyandu activities, on the fourth Tuesday of each month.